2006
DOI: 10.1093/toxsci/kfj155
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbital Induces Progressive Patterns of GC-Rich and Gene-Specific Altered DNA Methylation in the Liver of Tumor-Prone B6C3F1 Mice

Abstract: Altered DNA methylation contributes to tumorigenesis by affecting gene expression in a heritable fashion. Phenobarbital (PB) is a nongenotoxic rodent carcinogen which induces global hypomethylation and regions of hypermethylation in mouse liver. Liver tumor-sensitive (B6C3F1) and -resistant (C57BL/6) male mice were administered 0.05% (wt/wt) PB in drinking water for 2 or 4 weeks, and a 2-week recovery was included following each dosing period. DNA was isolated from liver (target) and kidney (nontarget) tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 28 publications
1
49
1
Order By: Relevance
“…Exposure to the NGC phenobarbital (PB) can lead to an increase in the incidence of spontaneously and chemically induced liver tumors in rodents and significantly promotes hepatic tumor incidence in B6C3F1 mice, as well as increasing the size of the tumors themselves [95][96][97][98][99].…”
Section: Function and Distributionmentioning
confidence: 99%
“…Exposure to the NGC phenobarbital (PB) can lead to an increase in the incidence of spontaneously and chemically induced liver tumors in rodents and significantly promotes hepatic tumor incidence in B6C3F1 mice, as well as increasing the size of the tumors themselves [95][96][97][98][99].…”
Section: Function and Distributionmentioning
confidence: 99%
“…Thus, several nongenotoxic chemicals have been found to affect gene function through changes in DNA methylation (27). For example, the nongenotoxic rodent carcinogen phenobarbital induces global hypomethylation and regional hypermethylation in rodent livers (28,3,29). MiRNAs are a group of regulatory RNAs of 19e22 nucleotides involved in posttranscriptional gene regulation (30).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term treatment with non-genotoxic rodent carcinogens, including peroxisome proliferators, is known to lead to hypomethylation of DNA and proto-oncogenes in mouse liver, events that were suggested to correlate with a burst of cell proliferation [11][12][13]. Our previous studies using a methyl-deficient model of non-genotoxic hepatocarcinogenesis in rats showed that alteration of cellular epigenetic processes, such as DNA hypomethylation and loss of histone H4 lysine 20 trimethylation, are key steps in the carcinogenic process induced by methyl deficiency [14,15].…”
Section: Introductionmentioning
confidence: 99%